2015
DOI: 10.1039/c5ra10499h
|View full text |Cite
|
Sign up to set email alerts
|

SnCl4 or TiCl4: highly efficient catalysts for the detetrahydropyranylation and demethoxymethylation of phenolic ethers and sequential one-pot asymmetric synthesis of 3-aryl-2-hydroxy-2,3-dihydroindan-1-ones from chalcone epoxides

Abstract: SnCl4 or TiCl4 catalysts provide a rapid and efficient detetrahydropyranylation and demethoxymethylation of phenolic ethers and a sequential one-pot intramolecular Friedel–Crafts alkylation of chalcone epoxides under mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…172 In 2015, Ahmed and co-workers reported the FC reaction of racemic and enantiomerically enriched chalcone epoxide substrates via an EAC strategy with catalytic TiCl 4 or SnCl 4 and resulting trans-3-aryl-2-hydroxy-2,3-dihydro-1H-inden-1-ones. 173 Furthermore, Das reviewed FC intramolecular C-C bondforming reactions of arene or heteroarene nucleophiles with tethered epoxides starting materials. 174 In 2010, Qu and Li studied the FC alkylation of arene nucleophiles with epoxides promoted by HFIP or water under refluxing conditions.…”
Section: Short Review Synthesismentioning
confidence: 99%
“…172 In 2015, Ahmed and co-workers reported the FC reaction of racemic and enantiomerically enriched chalcone epoxide substrates via an EAC strategy with catalytic TiCl 4 or SnCl 4 and resulting trans-3-aryl-2-hydroxy-2,3-dihydro-1H-inden-1-ones. 173 Furthermore, Das reviewed FC intramolecular C-C bondforming reactions of arene or heteroarene nucleophiles with tethered epoxides starting materials. 174 In 2010, Qu and Li studied the FC alkylation of arene nucleophiles with epoxides promoted by HFIP or water under refluxing conditions.…”
Section: Short Review Synthesismentioning
confidence: 99%
“…According to the literature, ring opening of styrene oxide by arenes with moderate nucleophilicities occurs only in the presence of strong Lewis acids (AlCl 3 , SnCl 4 , and others) or strong Brønsted acids (e.g., trifluoromethanesulfonic acid). In 2010, we reported that HFIP promotes intramolecular Friedel–Crafts reactions between arenes and epoxides .…”
Section: Resultsmentioning
confidence: 99%
“…Ahmed and co‐workers reported an efficient protocol for the detetrahydropyranylation and demethoxymethylation of phenolic ethers and the stereoselective synthesis of trans ‐2‐hydroxy‐3‐aryl‐1‐indanone derivatives 54 [46] . The reaction proceeds via sequential ring opening of the chalcone epoxides 53 and intramolecular Friedel‐Crafts alkylation in the presence of SnCl 4 (or TiCl 4 ) catalyst (Scheme 18).…”
Section: Acid‐catalyzed Synthesismentioning
confidence: 99%